Convective drying of a moist porous object under the effects of a rotating cylinder in a channel - Selimefendigil, Fatih; Ozcan Coban, Seda; Öztop, Hakan Fehmi (Springer, 2020)
Numerical study of evaporation in porous medium during convective drying process was examined, and heat and mass transfer of liquid water and water vapor through porous media was investigated by using the Galerkin weighted residual finite element method. The porous moist object has a rectangular shape and is assumed to represent a food sample. Two-dimensional laminar flow of dry hot air was used in the channel with a rotating circular cylinder. Different locations and angular rotational speed of the rotating cylinder were considered to control the convective heat transfer and mass transportation. The radius of rotating cylinder and velocity of drying air were also varied with five different values. Results showed that rotational angular speed and drying air velocity had significant effect on heat transfer and mass transport phenomenon for the porous moist object.
Keywords: Convective drying; Heat and mass transfer; Porous matrix; CFD